Pyrolysis of Palm Kernel Shell to Chemicals by Using Bayah Natural Zeolites (Universitas Negeri Semarang, 2020)
Palm kernel shell (PKS) is one of the biomass with high potential that can be converted into chemicals. In this study, palm kernel shell (PKS) was converted by pyrolysis method to produce condensed liquid products, gas, and solid. The purpose of this study was to determine the effect of catalyst activation time on yields and characteristics of PKS waste pyrolysis products. The pyrolysis process was carried out at a temperature of 500oC. Based on the results obtained with the addition of catalysts at 7 hr of activation can reduce the yield of solid products by 1.5% wt and 9.01% wt of liquid and increase the yield of gas products by 10.51% wt. On the characteristics of solid product there is a decrease in volatile matter by 55.04% wt and an increase fixed carbon by 40.27% wt. The gas characteristics, the H2 and CO gas decreases by 5.43% v/v and 1.36% v/v and the increase in CH4 and CO2 gas by 1.07% v/v and 5.72% v/v. Characteristics of the liquid obtained an increase in the amount of acetic acid by 11.75% v/v and decrease phenol compounds by 13.08% v/v. The result liquid product can be applied as a chemical.